Currium development in language teaching - Richards, Jack C. (Cambridge University Press, 2009)
This text provides a systematic introduction to the issues involved in developing, managing, and evaluating effective second and foreign language programs and teaching materials. Key stages in the curriculum development process are examined, including situation analysis, needs analysis, goal-setting, syllabus design, materials development and adaptation, teaching and teacher-support, and evaluation. Taken into account are such factors as program content, program context, learner needs, teaching aims and objectives, and the selection of instructional materials. Practical task and discussion activities throughout the book enable it to be used both in in-service courses and as a reference text for coordinators, teachers, and program administrators.